(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigates the implications of climate change for occupational health risks among civil servants in Rivers State. The need for this study arises from the increasing impact of climate change on work environments. Many government offices lack adequate measures to protect workers from climate-related hazards. This study used a descriptive survey research design. A sample of 300 civil servants was selected from various ministries in Rivers State through random sampling. Data was collected using a structured questionnaire. The data was analyzed using mean scores and chi-square tests. Findings showed that climate change significantly increases occupational health risks. These risks include heat stress, increased disease exposure, and mental health issues. However, challenges such as poor workplace infrastructure, lack of awareness, and insufficient government policies hinder effective adaptation. The study concludes that climate change is a major threat to the health and productivity of civil servants. It recommends the development of specific occupational health policies, improvement of workplace facilities, and training programs to build resilience against climate change impacts.